2018
DOI: 10.1038/s41598-018-32681-y
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal value of sunflower pollen against bee pathogens

Abstract: Global declines in pollinators, including bees, can have major consequences for ecosystem services. Bees are dominant pollinators, making it imperative to mitigate declines. Pathogens are strongly implicated in the decline of native and honey bees. Diet affects bee immune responses, suggesting the potential for floral resources to provide natural resistance to pathogens. We discovered that sunflower (Helianthus annuus) pollen dramatically and consistently reduced a protozoan pathogen (Crithidia bombi) infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
154
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 101 publications
(165 citation statements)
references
References 66 publications
9
154
2
Order By: Relevance
“…In the second experiment, we demonstrated that 7 days of sunflower pollen, post-infection, suppressed C. bombi infections to nearly undetectable levels while 7 days of buckwheat pollen resulted in a relatively high C. bombi infection, consistent with previous work (Giacomini et al, 2018). Although exposure to 3.5 days of sunflower pollen immediately following infection was not as effective as exposure for 7 days, it was more effective than consuming only buckwheat pollen.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…In the second experiment, we demonstrated that 7 days of sunflower pollen, post-infection, suppressed C. bombi infections to nearly undetectable levels while 7 days of buckwheat pollen resulted in a relatively high C. bombi infection, consistent with previous work (Giacomini et al, 2018). Although exposure to 3.5 days of sunflower pollen immediately following infection was not as effective as exposure for 7 days, it was more effective than consuming only buckwheat pollen.…”
Section: Discussionsupporting
confidence: 88%
“…Palmer-Young et al 2017). Furthermore, sunflower pollen reduced two pathogens in two different hosts, C. bombi in B. impatiens and N. ceranae in A. mellifera (Giacomini et al, 2018). Furthermore, sunflower pollen reduced two pathogens in two different hosts, C. bombi in B. impatiens and N. ceranae in A. mellifera (Giacomini et al, 2018).…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations